2022
DOI: 10.1080/21645515.2022.2074716
|View full text |Cite
|
Sign up to set email alerts
|

Hesitancy of COVID-19 vaccines: Rapid systematic review of the measurement, predictors, and preventive strategies

Abstract: Vaccine hesitancy is one of the top ten global health threats and the first threat to fighting COVID-19 through vaccination. With the increasing level of COVID-19 vaccine hesitancy amidst the rising level of confirmed cases and death tolls, this paper provides rapid systematic literature reviews on the measurement of COVID-19 vaccine hesitancy, key determinants and evidence-based strategies to prevent COVID-19 vaccine hesitancy. The findings reveal three standard measures of vaccine hesitancy: optional respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 40 publications
1
45
1
1
Order By: Relevance
“…The current situation necessitates the administration of COVID-19 vaccines in children, but still, vaccine hesitancy has become a global challenge (18). Although the vaccine hesitancy varies across the globe and is terrifyingly high in many regions encompassing substantial proportion of world's population, the vaccination rate is below the average number required for herd immunity and rates of vaccination intentions are declining especially among parents of young children despite recent advances (19). "Parental vaccine hesitancy is defined as the delay in the acceptance or refusal of vaccines from parents of Frontiers in Pediatrics 02 frontiersin.org children despite their availability" (20).…”
Section: Introductionmentioning
confidence: 99%
“…The current situation necessitates the administration of COVID-19 vaccines in children, but still, vaccine hesitancy has become a global challenge (18). Although the vaccine hesitancy varies across the globe and is terrifyingly high in many regions encompassing substantial proportion of world's population, the vaccination rate is below the average number required for herd immunity and rates of vaccination intentions are declining especially among parents of young children despite recent advances (19). "Parental vaccine hesitancy is defined as the delay in the acceptance or refusal of vaccines from parents of Frontiers in Pediatrics 02 frontiersin.org children despite their availability" (20).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, an association with a specific age category has not been proven. Another predictor can be the employment status: some studies found that some occupations, for example, healthcare workers, are less hesitant to COVID-19 vaccination [ 20 ]. However, other studies showed that employment status was not significantly associated with vaccination willingness [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is a wealth of evidence in the scientific literature on strategies and actions to combat vaccine hesitancy [ 24 , 25 ].…”
Section: The Ten Actions Suggested By the Italian Society Of Hygiene ...mentioning
confidence: 99%